THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF LAND RESOURCE MANAGEMENT MECHANISMS OF AGRARIAN ENTERPRISES - POLTAVETS, ANATOLII (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article substantiates the theoretical and methodological foundations of the formation and functioning of land resources management mechanisms of agrarian enterprises. It was established that land resources, as an object of management, involves taking into account the peculiarities of their participation in economic circulation, as well as economic, ecological and social aspects of the reproduction of resources placed in production and commercial processes. It is well established that the main criteria for effective land use by agricultural enterprises are obtaining production results sufficient for extended reproduction of advanced capital in the form of produced volumes of agricultural products, provided that the agro-ecological condition of agricultural lands is improved and the proper level of income of landowners is achieved. It was determined that one of the key measures in the management system of the use of land resources is the placement of crop rotations taking into account the production and commodity specialization of agricultural enterprises. It has been established that the elements of the mechanism of sustainable land use include not only economic and ecological components, but also mechanisms for monitoring and assessing land resources, as well as financial mechanisms for compensation for environmental damage. Four measures have been identified to improve the use of land resources within the framework of the land resources management mechanism in the management system of agrarian enterprises: improvement of the state of land resources of agrarian enterprises; reduction of removal of land from agricultural circulation, compensation of losses from non-agricultural users, reduction of pollution of land resources; use of vacant land suitable for agricultural purposes; rationalization of the use of the land fund from the point of view of the final results of agricultural production.
Keywords: land resources; management mechanisms; efficiency; restoration; sustainable land use